Studi Optimasi Distribusi Air Irigasi Di Daerah Irigasi Lodoyo - Ekorini, Lucky Dyah; Limantara, Lily Montarcih; Suhartanto, Ery (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
Lodoyo Irrigation Area covers two districts namely Blitar and Tulungagung. Irrigation Area Lodoyo itself has intakes in Dam Wlingi in Blitar. Wlingi dam located on the Brantas River in the Village District Jegu Sutojayan Blitar Â± 30 km in the downstream dam Sutami. The expected benefits and purpose of the construction of this dam is Wlingi Raya for the supply of irrigation water and generate hydropower. Irrigated area has a wide DI Lodoyo raw rice 12,219 ha, comprising 12 204 irrigation and 15 ha for ponds. Types of crops grown in the area of DI Lodoyo for each growing season are: (1) rainy season, planting season I: Rice - Crops; (2) Dry Season I, II Planting season: Rice - Crops; (3) Dry Season II, Planting season III: Rice - Crop. While the availability of discharge in irrigated areas Lodoyo is based on the availability of existing discharge in the Brantas River, in this case is Wlingi Reservoir catchment. Based on the results of the optimization analysis conducted extensive rice plants obtained optimum results: in dry conditions 4,041 ha, 4,242 ha under normal conditions;, in wet conditions: 4,682 ha. While the results of the maximum benefit in dry conditions Rp. 58,780,404,629.00; under normal conditions Rp. 59,792,367,463.00;, in wet conditions Rp. 62,009,795,069.00. To obtain the results of the sensitivity analysis results are sensitive land: in dry conditions between 2844-15359 ha; under normal conditions between 3051-15999 ha while in wet conditions between 305117400 ha.Keywords : Irrigation, Optimization, Sensitivity